Potential of Bamboo as Car Roof Material - D. L. Zariatin; Josep Krisdiandi Sibarani; Dahmir Dahlan; Ralf Förster; Ziani Adriant (Fakultas Teknik Universitas Pancasila, 2022)
An effort to achieve SDGs 12# responsible for consumption and production is by optimizing the application of natural recycled materials, such as bamboo, in the automotive industry. Bamboo is a potential insulating material because it has low thermal conductivity. This study used Gigantochloa Atroviolacea as a thermal insulator projected as a car roof. Experiments were performed to identify the effective thermal conductivity. There were two shapes tested: slab and box. The first specimen is a laminated bamboo slab, and the second is a combined slab of laminated bamboo, glass wool, and aluminum foil. Based on the heat transfer calculation, the effective thermal conductivity is 0.21 W/mK and 0.14 W/mK for the laminated bamboo slab and combined slab, respectively. The thermal flow characteristic was analyzed in two box models with different material arrangements. The first box is laminated bamboo and fiber, and the second is laminated bamboo and glass wool. The results show that the first box can insulate heat better than the second. It was concluded that laminated bamboo and bamboo fiber can be used as a substitute for glass wool material. The bending test of laminated bamboo with three different layers was performed according to ASTM D 790. The maximum load was 616 kg for five layers. The bending test showed that laminated bamboo is insufficient as a car roof. Steel plates are still necessary to comply with the requirements of the FMVSS 216 standard.